Hubungan Sanitasi Lingkungan dengan Kejadian Infeksi Soil Transmitted Helminths pada Anak Sekolah Dasar di Jember - Nur Aqmarina Kusumawardani; Erma Sulistyaningsih; Cicih Komariah (Pustaka Kesehatan, 2019)
Poor environmental sanitation is suspected to be one of the causes of soil transmitted helminthes (STH) infection. Environmental sanitation consists of water sources, latrine, sewerage, garbage disposal facilities, and floor type. The objective of this study was to investigate the relationship between environmental sanitation and the incidence of STH infection in primary school children. This was an observational analytic study with cross-sectional design. The subjects were 80 students of two elementary schools in Jember. Stool samples were collected and examined by Kato-Katz method. Data of environmental sanitation was collected by questionnaire and direct observation. Kato-Katz examination showed that 9 samples (11,3%) infected by Ascaris lumbricoides. The majority respondents had not fulfilled requirements of good environmental sanitation. The result of Spearman test showed that there was a significant correlation between STH infection and latrine (p=0,02) but there were no significant relationship between STH infection and environmental sanitation (p = 0.165), gender (p = 0,669), age (p = 0,92), water source (p = 0.084), sewerage (p = 0.146), garbage disposal facilities (p = 0,728), and floor type (p = 0,065).